PROTOTIPE SISTEM KONTROL SUHU DAN PEMANTAUAN DAYA LISTRIK DI KAMAR KOS MENGGUNAKAN TEKNOLOGI IOT (INTERNET OF THINGS) - Raka Firmansyah; Bustanul Arifin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The increasing demand for electrical energy drives the need for a more efficient monitoring and control system. This study designs and tests a prototype of an IoT-based temperature control and electrical power monitoring system applied to a boarding room. The system uses NodeMCU ESP8266 as the main microcontroller, PZEM-004T sensor for measuring voltage, current, and power, DHT22 sensor for temperature and humidity, a relay module as a load controller, and the Arduino IoT Cloud platform for remote monitoring and control via a website. Electrical and temperature parameters are displayed locally via OLED and online through a web dashboard. The research methods include literature study, system design, hardware and software assembly, as well as testing and measuring device performance. The testing was conducted on a load consisting of two lamps and one fan with a voltage of 220 VAC. The measurement results show that the system is capable of reading electrical parameters with a small margin of error, where the display difference between the OLED and the website is relatively low. The system also successfully performs remote control functions with stable relay responses to commands from the website. Based on these results, the prototype is considered capable of operating accurately, in real-time, and reliably in monitoring and controlling small-scale electricity consumption. This system has the potential to help improve energy efficiency, particularly in simple residential settings such as boarding rooms, and can be further developed for larger-scale applications with enhancements in security, network reliability, and automatic notification features.